Commercialization of Intellectual Property Rights in Kenyan Universities - Amenya, DM; Wekesa, M (Research and Advances in Education, 2025)
This study examined the commercialization of intellectual property (IP) rights within Kenyan universities, focusing on the level of IP awareness among university staff, as well as the current state of institutional IP policies. With declining government funding and an increasing demand for innovation-driven revenue, universities faced mounting pressure to transform research outputs into commercially viable products. However, several challenges, such as limited awareness, inadequate policies, and weak institutional linkages, continued to hinder this process. A mixed-method research design was employed, utilizing a structured questionnaire administered via the KoboCollect Toolbox. A total of 52 respondents from both public and private universities participated, resulting in a 94.5% response rate. Findings revealed that 59.6% of staff reported the existence of Technology Transfer or IP offices and formal IP policies within their institutions. Regular IP seminars were uncommon (21.2%), and only half of respondents rated their IP knowledge as “good.” Commercialization activity was modest and skewed toward books (28.8%) and software sales (30.8%). Private universities outperformed public counterparts in securing patents, trademarks, and copyrights, whereas public institutions showed relative strength in industrial designs and traditional medicine protections. Among the recommendations is the need for a longitudinal study to assess the developmental trajectory of universities towards embracing IP fully.